2022
DOI: 10.1055/s-0042-1758455
|View full text |Cite
|
Sign up to set email alerts
|

Chronic inflammatory demyelinating polyneurophaty: assessment of the cognitive function and quality of life

Abstract: Background Studies were carried out with the objective of evaluating the quality of life (QoL) of patients affected by chronic inflammatory demyelinating polyradiculopathy (CIDP). However, the cognitive issue is still little addressed. Objectives To assess the QoL and cognitive impairment of patients with CIDP and to analyze whether there is a correlation between these parameters. Methods Seven patients with CIDP and seven paired controls were subjected to: mini-mental state examination (MM… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 14 publications
(31 reference statements)
0
2
0
Order By: Relevance
“…This particular result is of note, since knowledge about non‐physical consequences of CIDP is altogether scarce. In particular, studies on CIDP‐related quality of life changes raised the question of whether also non‐physical factors contribute to reduced quality of life [43–46]. Mostly, this research showed increased pain, depressiveness, anxiety or fatigue as clinical problems, whereas cognitive dysfunction has only consistently been shown in one previous trial to our knowledge [1, 43–46].…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…This particular result is of note, since knowledge about non‐physical consequences of CIDP is altogether scarce. In particular, studies on CIDP‐related quality of life changes raised the question of whether also non‐physical factors contribute to reduced quality of life [43–46]. Mostly, this research showed increased pain, depressiveness, anxiety or fatigue as clinical problems, whereas cognitive dysfunction has only consistently been shown in one previous trial to our knowledge [1, 43–46].…”
Section: Discussionmentioning
confidence: 98%
“…In particular, studies on CIDP‐related quality of life changes raised the question of whether also non‐physical factors contribute to reduced quality of life [43–46]. Mostly, this research showed increased pain, depressiveness, anxiety or fatigue as clinical problems, whereas cognitive dysfunction has only consistently been shown in one previous trial to our knowledge [1, 43–46]. Against this background, a comprehensive assessment of a potential cognitive impact of CIDP seems worthwhile for pragmatic reasons.…”
Section: Discussionmentioning
confidence: 99%